EFEK IMUNOMODULATOR EKSTRAK DAUN ASAM JAWA (Tamarindus indica L) TERHADAP JUMLAH DAN JENIS SEL LEUKOSIT PADA MENCIT BALB/C YANG DIINFEKSI BAKTERI Salmonella Typhi - mala aulia hapsari; Meka Faizal Farabi (LPPM Universitas Abdurrab, 2025)
Typhoid fever is an acute infectious disease caused by Salmonella typhi germs, mainly affecting the digestive tract with symptoms of fever for more than 7 days. In Indonesia alone, the incidence rate for this disease is estimated to be around 300-810 cases per 100,00 population per year. Tamarind leaves with flavonoid content can inhibit anti-inflammatory activity. This study aims to determine the immunomodulatory effect of tamarind leaf extract (Tamarindus indica L). Against the number and type of leukocyte cells in balb/c mice infected with Salmonella typhi bacteria. In this study using the experimental group method of Balb/c male mice. Pure form (Tamarindus indica L.) shows immunomodulatory activity such as an increase in the number and type of leukocytes. The research sample was 25 Balb/c male mice weighing 20-30 grams which were then divided into 5 treatment groups. The dose variation is 50 mg/kg BW, 75 mg/kg BW, and 100 mg/kg BW orally for 6 days. Then on day 7 was infected using Salmonella typhi bacteria. Statistical test results showed that the dose groups of 50, 75, and 100 mg/kg BW were not significantly different from the negative control (p>0.05).